Resources organizations social service: how to improve the quality of management - O. V. Nikonova (Путеводитель предпринимателя, 2020)
The article discusses issues related to the development of effective internal processes for management of financial and economic activities and development of the system of internal control use of resources at the disposal of social service organizations.